The Persian Tradition of Marriage Documentation: Pre-Islamic and Islamic Marriage Contacts - Zekrgoo, Amir H. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Persian Tradition of Marriage Documentation: Pre-Islamic and Islamic Marriage Contacts